Pregnant, miserable, and starving in 21st century America - Marlena S. Fejzo, PhD; Kimber W. MacGibbon, RN; Katherine L. Wisner, MD, MS (Elsevier, 2023)
Severe nausea and vomiting of pregnancy is too common and devastating to be trivialized any longer. Authors of recent studies observed that children exposed in utero to severe nausea and vomiting of pregnancy had an increased risk for autism spectrum disorder, a decreased brain cortical volume, and developmental deficits. Research on severe nausea and vomiting of pregnancy and hyperemesis gravidarum has been disturbingly slow. It was not until 2021 that an international consensus definition was published. Hyperemesis gravidarum starts before 16 weeks' gestation, is characterized by severe nausea with or without vomiting and an inability to eat and drink normally, and greatly limits daily activities. Maternal misery is caused by unrelenting nausea, intractable retching or vomiting, ptyalism, dehydration, reflux, malnutrition, and social isolation. Hyperemesis gravidarum is the second most common reason for hospitalization in pregnancy. Symptoms can persist until delivery in one-third of individuals who experience extreme weight loss. Significant associations have been identified between hyperemesis gravidarum and multiple adverse outcomes. Maternal deaths owing to hyperemesis gravidarum continue to be reported, and hyperemesis gravidarum is associated with high fetal loss and termination rates. These grim findings highlight the critical public health importance of treating severe nausea and vomiting of pregnancy early to mitigate serious complications that compromise maternal and offspring health during pregnancy and beyond. Despite suffering extreme debility, individuals with hyperemesis gravidarum report feeling that their experiences were dismissed by healthcare professionals, contributing to therapeutic termination, suicidal ideation, perinatal depression, and posttraumatic stress disorder. Hyperemesis gravidarum must be recognized early and treated aggressively with frequent monitoring. Although medications can be effective in reducing symptoms, many patients do not gain adequate relief, and new treatments are needed. A promising new avenue for treatment comes from genetic discoveries. The gene, growth differentiation factor-15, which codes for a nausea and vomiting hormone produced by the placenta, is the greatest genetic risk factor for hyperemesis gravidarum, and therapies are currently in clinical trials in cancer. However, until treatment is universally effective, abortion access must be available for refractory hyperemesis gravidarum. Herein, we emphasize data published since the most recent American College of Obstetrics and Gynecology report (2018), such as long-term neuropsychiatric consequences in offspring exposed to hyperemesis gravidarum and suggest interventions anticipated to prevent progression of early symptoms to hyperemesis gravidarum.